2019
DOI: 10.1111/plb.12974
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology of the Neotropical gesneriad Gloxinia perennis: chemical composition and temporal fluctuation of floral perfume

Abstract: Although common among orchids, pollination by perfume-gathering male euglossine bees is quite rare in other Neotropical families. In Gesneriaceae, for example, it is reported in two genera only, Drymonia and Gloxinia. Flowers of G. perennis are known to emit perfume, thereby attracting male euglossine bees as pollinators. However, detailed reports on the pollination ecology, as well as on chemistry of floral perfume of individuals in natural populations, are still missing. In this study, we report on the polli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In contrast, visual cues and floral scents are common in bee‐pollinated species (Dobson, ). Interestingly, of the four scents in A. flava , 1,8‐cineole and α‐pinene are commonly found in flowers pollinated by male euglossine bees, and tetradecane is common in flowers pollinated by nectar‐seeking bees (Gerlach and Schill, ; Dobson, ; Martel et al ). In contrast, terpenoids such as 1,8‐cineole and limonene are apparently not well perceived by butterflies (Andersson and Dobson, ); thus, the function of limonene in flowers of A. patens needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, visual cues and floral scents are common in bee‐pollinated species (Dobson, ). Interestingly, of the four scents in A. flava , 1,8‐cineole and α‐pinene are commonly found in flowers pollinated by male euglossine bees, and tetradecane is common in flowers pollinated by nectar‐seeking bees (Gerlach and Schill, ; Dobson, ; Martel et al ). In contrast, terpenoids such as 1,8‐cineole and limonene are apparently not well perceived by butterflies (Andersson and Dobson, ); thus, the function of limonene in flowers of A. patens needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…8 Perfume flowers have appeared independently in several Neotropical families under distinct evolutionary/ecological contexts. Similar to C. burle-marxii, it is also likely that the only case of pollination by male euglossine bees among Gesneriaceae, i.e., Gloxinia perennis, 53 has evolved in a clade having hummingbirds as ancestral pollinators. 54 More frequently, however, perfume flowers are derived from food-deceptive flowers pollinated by male and female euglossine and/or non-euglossine bees (Orchidaceae: Catasetinae, Zygopetalinae, and Stanhopeinae) 55,56 from resin-(Euphorbiaceae: Dalechampia) 57,58 and pollen-rewarding flowers (Solanaceae: Cyphomandra) 59,60 pollinated by female bees (usually from euglossine) or from beetle-pollinated species offering food and/or mating sites (Araceae: Anthurium and Spathiphyllum 61 and Annonaceae: Unonopsis 62,63 ).…”
Section: Perfume Flowers: Ecological and Evolutionary Perspectivesmentioning
confidence: 99%
“…This species is frequently sampled in faunistic inventories (e.g. Pires et al 2013;Silveira et al 2015;Machado et al 2018) and reported in a wide range of ecological studies related to pollination in agroecosystems (Marques et al 2017;Gutiérrez-Chacón et al 2018), pollination of plants in Amazon rainforest (Martel et al 2019;Watteyn et al 2021), and as vectors of cleptoparasitic beetles (Rocha-Filho and Garófalo 2015).…”
Section: Introductionmentioning
confidence: 99%